2013
DOI: 10.1089/aid.2012.0192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tuberculosis on the Kinetics of CD4+T Cell Count Among HIV-Infected Patients Who Initiated Antiretroviral Therapy Early After Tuberculosis Treatment

Abstract: The effects of tuberculosis (TB) on the kinetics of CD4(+) T cells among HIV-infected individuals with early combination antiretroviral therapy (cART) after TB therapy initiation are poorly characterized. We conducted a case-control study with 15 HIV-TB-coinfected patients who initiated TB treatment and early cART, and 30 controls without TB who had similar CD4(+) T cell counts and viral loads at the time of starting cART. We compared the rate of CD4(+) T cell increase for 5 years after cART. The time to CD4(+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
1
8
1
Order By: Relevance
“…Another study from sub-Saharan Africa has also reported no difference in the immune recovery of HIV-infected individuals with or without TB co-infection after starting cART 38 . These ndings contrast with reports from high-income settings, which have linked the failure of immune recovery among cART-treated individuals to the levels of viral suppression 39,40 . These divergent results are probably affected by additional variables, such as the quality and accessibility of public health systems, genetic diversity, degrees of virological suppression, the timing of treatment initiation, and the speci c type of cART provided to individuals across various cohort settings.…”
Section: Discussioncontrasting
confidence: 97%
“…Another study from sub-Saharan Africa has also reported no difference in the immune recovery of HIV-infected individuals with or without TB co-infection after starting cART 38 . These ndings contrast with reports from high-income settings, which have linked the failure of immune recovery among cART-treated individuals to the levels of viral suppression 39,40 . These divergent results are probably affected by additional variables, such as the quality and accessibility of public health systems, genetic diversity, degrees of virological suppression, the timing of treatment initiation, and the speci c type of cART provided to individuals across various cohort settings.…”
Section: Discussioncontrasting
confidence: 97%
“…Our study also showed significant difference among TB co-infected individuals ( p = 0.016). This finding is also in line with a study conducted in South Korea [ 23 ]. This might be explained as TB infection impairs cellular immune responses through M. tuberculosis induced apoptosis of CD4+ cells which subsequently lead to depletion of CD4+ cells and results in poor immunological recovery despite viral suppression [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…In light of this, cHIV/HBV was previously shown to result in slow CD4+ T-cell recovery in these patients compared to PLWHIV only [ 9 , 42 ]. TB also results in slow CD4+ T-cell recovery even after ART initiation [ 43 , 44 , 45 ]. In one South Africa cohort of 15,646 adults, there was no difference in immune restoration between participants with cHIV/TB and those without TB after ART initiation [ 46 ].…”
Section: Discussionmentioning
confidence: 99%